Elimination of Subterranean Termite Colonies With Hexaflumuron in an Improved Bait Matrix, Preferred Textured Cellulose (PTC) - Leng, Choy Lee; Mohd Shah, Zahriman; Sajap, Ahmad Said (2009)
An improved, cellulosic bait matrix (Preferred Textured Cellulose, PTC) containing 0.5% hexaflumuron was tested against field colonies of the subterranean termites Coptotermes gestroi and Schedorhinotermes sp. in Malaysia. Of the eight colonies of C. gestroi detected, six were estimated for population size using dyed blank bait before treatment. Then, the colonies were treated with hexaflumuron-PTC baits. Bait consumption and days to colony elimination were estimated. All of the eight colonies were eliminated between 42-77 days (mean = 60 days) with estimated bait consumption of 22.93-167.00 g (mean = 60.17 g) which is equivalent to 114-835 mg of hexaflumuron. A Schedorhinotermes sp. colony appeared in one of the sites within two months after the elimination of C. gestroi. The Schedorhinotermes colony was baited with hexaflumuron-PTC bait and eliminated after 59 days with an estimated 48.85 g of bait consumed. While the effect of PTC bait on Coptotermes sp. showed no difference from that of Laminated Textured Cellulose (LTC) matrices, the PTC matrices showed increased palatability to other termite species such as Schedorhinotermes and Microtermes pakistanicus.